Seducir, levantar, estabilizar: amor y política entre varones gays argentinos - Marentes, Maximiliano (2022)
This paper analyzes how loving and political trajectories of Argentinean gay men are intersected. In doing so, the goal is to critically review love self-referentiality’s hypothesis operating in contemporary societies and develop the complexity of the notion of sociability to explain political paths. The methodological approach was based in conducting in-depth interviews with 30 gay men who live in the Metropolitan Area of Buenos Aires to reconstruct their love stories. I identify three ways in which love and politics are intertwined. The first one refers to how politics becomes a principle of seduction. The second one implies thinking politics as a hooking-up space. The third one describes the ways through which politics contribute to stabilize couples. I conclude that the description of those crossroads advances in the understanding of love, relativizing self-referentiality’s hypothesis sustained in social studies of love, and unfolding the non-politics category, included in politization studies.